The impact of concomitant administration of vanadium and insulin on endothelial dysfunction markers (PAI-1 and ET-1) in type 1 diabetic rats. (2nd January 2021) - Morsy, M. D.; Bin-Jaliah, I.; Bashir, S. O.; Shatoor, A.; Haidara, M. A.
Abstract: Endothelial dysfunction in type 1 diabetes mellitus (T1DM) is an important factor in the pathogenesis of micro- and macrovascular complications. The present study was to investigate the impact of combined vanadium and insulin for proper control and protection against endothelial dysfunction in T1DM rats. Sixty male Sprague-Dawley rats were randomly divided into six groups; control non-treated; control vanadium treated; T1DM; T1DM + insulin; T1DM + vanadium; T1DM + insulin + vanadium treated groups. At the end of the experiment (6 weeks), serum C-reactive protein, tumour necrosis factor-alpha, IL-6, endothelin-1, plasminogen activator inhibitor-1, fasting glucose serum lipogram, liver homogenate SOD activity and MDA levels were determined. Concomitant insulin and vanadium treatment improved the diabetic metabolic disturbances in addition to endothelial dysfunction and inflammatory markers. We can conclude that concomitant administration of both vanadium and insulin in T1DM decreased the risk for the development of endothelial dysfunction, micro- and macrovascular complications.